2021
DOI: 10.1159/000517327
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide Study of the Prevalence and Initial Management of Atypical Genitalia in the Newborn in Scotland

Abstract: Provision of optimum healthcare for infants with atypical genitalia requires a clear understanding of the occurrence of this condition. The objective of this study was to determine the prevalence of atypical genitalia and its initial management. A prospective, electronic survey of clinicians within managed clinical networks in Scotland was undertaken between 2013 and 2019. Notification from clinicians was sought for term neonates requiring specialist input for atypical genitalia. Additional information was als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 18 publications
1
11
1
Order By: Relevance
“…Previously, Thyen et al [ 9 ] have suggested a birth prevalence of 1:5000 in Germany, which is similar to our data. In contrast, Rodie et al [ 10 ] have recently reported a birth prevalence of children requiring specialist assessment for atypical genitalia of 1:3318 in Scotland, although 68% of these children were assigned at birth before the results of more detailed investigations, so more complex DSD may have a similar prevalence to in our study. Specifically focusing on CAH, national registry data from the British Paediatric Surveillance unit (August 2007-August 2009) suggested an overall CAH incidence of 1 in 18 000 children (1 in 13 000-15 000 in many countries), and that three-quarters of girls present in the newborn period with genital changes [ 11 ].…”
Section: Discussioncontrasting
confidence: 96%
“…Previously, Thyen et al [ 9 ] have suggested a birth prevalence of 1:5000 in Germany, which is similar to our data. In contrast, Rodie et al [ 10 ] have recently reported a birth prevalence of children requiring specialist assessment for atypical genitalia of 1:3318 in Scotland, although 68% of these children were assigned at birth before the results of more detailed investigations, so more complex DSD may have a similar prevalence to in our study. Specifically focusing on CAH, national registry data from the British Paediatric Surveillance unit (August 2007-August 2009) suggested an overall CAH incidence of 1 in 18 000 children (1 in 13 000-15 000 in many countries), and that three-quarters of girls present in the newborn period with genital changes [ 11 ].…”
Section: Discussioncontrasting
confidence: 96%
“…Atypical genitalia at birth are the most common manifestation of DSD occurring in approximately 1 in 300 births [Ahmed et al, 2004]. However, genitalia that are sufficiently atypical to require any investigations during early infancy are rarer with a birth prevalence of about 1 in 1,200 in term infants [Rodie et al, 2022]. In addition, three-quarters of cases of atypical genitalia that present with a hypospadias have a 46,XY karyotype and are raised as boys [Ahmed et al, 2004;Rodie et al, 2022].…”
Section: Introductionmentioning
confidence: 99%
“…However, genitalia that are sufficiently atypical to require any investigations during early infancy are rarer with a birth prevalence of about 1 in 1,200 in term infants [Rodie et al, 2022]. In addition, three-quarters of cases of atypical genitalia that present with a hypospadias have a 46,XY karyotype and are raised as boys [Ahmed et al, 2004;Rodie et al, 2022]. A substantial proportion of these boys will be profoundly undermasculinised, and at least 20-25% may not have a satisfactory outcome [Al-Juraibah et al, 2019;Tack et al, 2020].…”
Section: Introductionmentioning
confidence: 99%
“…The newborn with atypical genitalia requiring specialist input occurs in approximately 1 in 3000 term births 18. In these cases, sex assignment of the affected child should not just be based on a simple extrapolation of future gender role behaviour from the appearance of the genitalia at birth, but on the best prognosis for future psychosocial and psychosexual function, taking into account the clinical presentation of the child, details of the clinical syndrome, likelihood of fertility as well as the possible effects of prenatal steroid exposure.…”
Section: Introductionmentioning
confidence: 99%
“…The family may also wish to wait until sex of rearing is known before they name the baby or announce the birth to others. In most cases, a decision can be reached within 2–3 working days 18 28. There remains significant social stigma around DSD conditions and parents may find it difficult to talk about this diagnosis with others, particularly in the initial days 25.…”
Section: Introductionmentioning
confidence: 99%